2020
DOI: 10.1002/cctc.202000624
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Intimacy and its Interplay with Metal‐Acid Balance in Shaped Hydroisomerization Catalysts

Abstract: The combined impact of platinum location and metal-acid balance on the catalytic performances of HUSY zeolite aluminashaped bifunctional catalysts was evaluated in n-hexadecane hydroconversion reaction. For well-balanced catalysts, the deposition of Pt in the alumina resulted in lower isomerization selectivity as compared to when platinum was located in the zeolite. In the latter case, the maximal distance between Pt and acid sites was found to be in the nanometric scale (high intimacy) whereas in the former i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…For more details on the n -C 16 hydroconversion mechanism, we refer the reader to literature. 3 , 5 , 47 , 87 89 …”
Section: Resultsmentioning
confidence: 99%
“…For more details on the n -C 16 hydroconversion mechanism, we refer the reader to literature. 3 , 5 , 47 , 87 89 …”
Section: Resultsmentioning
confidence: 99%
“…Both catalysts were experimentally found to be poorly balanced in pure n -octane hydrocracking (Figure a). For a lower metal site concentration, intermediate (cyclo)­alkenes are more prone to undergoing consecutive acid catalyzed reactions (also see Figure ), , with a concomitant impact on the product distribution.…”
Section: Discussionmentioning
confidence: 99%
“…A sufficiently high concentration of active metal sites compared to the Brønsted acid sites ensures that (de)hydrogenation reactions are in quasi-equilibrium (good balance of metal and acid sites). Moreover, apart from the ratio, also the distance between metal and Brønsted acid sites should also be sufficiently small such that transfer of intermediate (cyclo)alkenes does not become limiting 10,[13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Chen et al is one of the only studies currently published that benchmarked Ni-acid site distance, the dependence of metal-acid site distance on efficiency is a focus in the field of metal/acid hydrocracking. The efficiency of bifunctional metal-acid catalysts for hydrocracking has shown that mass transfer and site distance, which should be neither too close nor too far, can play an influential role [92][93][94][95][96][97][98][99]. Whether or not the significance of metal-acid distance also applies to nickel-acid oligomerization catalysts still remains to be addressed.…”
Section: Effect Of Metal-acid Site Distancementioning
confidence: 99%